Decision-Making Based on Social Conventional Rules by Elderly People - Komeda, Hidetsugu; Eguchi, Yoko; Kusumi, Takashi; Kato, Yuka; Narumoto, Jin; Mimura, Masaru (Frontiers in Psychology, 2018)
Information used by older adults engaging in a social decision making task of judging a protagonist as a good or a bad person was investigated. Older (n = 100, 50 women, mean age = 63.6 years) and younger (n = 100, 50 women, mean age = 25.7 years) adults participated in a web-based survey. In Experiment 1, we assessed participants’ rapid decision-making processes when making good or bad judgments after reading consecutive sentences without reviewing previously read sentences. The percentages of good judgments were analyzed. In Experiment 2, two characters engaging in a deliberate decision-making process were presented, and participants were asked to judge better and worse protagonists. The percentages of behavior-based judgments were analyzed. Results of Experiment 1 indicated that older adults judged protagonists as “good” more often than younger adults. Especially, older adults judged protagonists with good behavior as being “good.” In Experiment 2, older adults made behavior-based judgments more than younger people. Additionally, older and younger adults used information on personalities of protagonists for making judgments in situations with bad outcomes, or incongruent. Moreover, multiple regression analysis suggested that people with more general trust engaged more, whereas people with more caution engaged less in making behavior-based judgments.